Viewing Art in Different Contexts - Estrada-Gonzalez, Vicente; East, Scott; Garbutt, Michael; Spehar, Branka (Frontiers in Psychology, 2020)
While aesthetic experiences are not limited to any particular context, their sensorial, cognitive and behavioural properties can be profoundly affected by the circumstances in which they occur. Given the ubiquitous nature of contextual effects in nearly all aspects of behaviour, investigations aimed at delineating the context-dependent and context-independent aspects of aesthetic experience and engagement with aesthetic objects in a diverse range of settings are important in empirical aesthetics. Here, we analyse the viewing behaviour of visitors (N=19) freely viewing 15 paintings in the 20th century Australian collection room at the Art Gallery of New South Wales. In particular, we focus on how aspects of viewing behaviour including viewing distance in the gallery condition and eye gaze measures such as fixation count, total fixation duration and average fixation duration are affected by the artworks’ physical characteristics including size and image statistics properties such as Fourier amplitude spectrum, fractal dimension and entropy. In addition, the same artworks were viewed in the laboratory, either scaled to fit most of the screen (N=22) or to preserve their relative size as in the museum condition (N=17) to assess the robustness of these relationships across different presentation contexts. We find that the effects of presentation context are modulated by the artworks’ physical characteristics.